Interculturality and basic education, a study made in a Peruvian educational institute - Alarcón Díaz, Mitchell (2015)
The research was aimed to determine the differences between the levels of multiculturalism according to gender, place of origin, and the living experience with the traditional customs of students of high school No. 157 “José Abelardo Quiñones” (Peru). To reach this goal, the researchers implemented a study based on a quantitative approach, with a hypothetico-deductive method and a descriptive cross-sectional design. From the application of the intercultural traits instrument,  we conclude that there are significant differences, with a strong level tendency, in gender and customs living experiences of the students.